Advancing circular economy in industrial chemistry and environmental engineering: Principles, alignment with United Nations sustainable development goals, and pathways to implementation - Saeed, Salaha; Arshad, Muhammad Yousaf; Ahmed, Anam Suhail (European Journal of Chemistry, 2023)
This groundbreaking review explores the crucial role of the circular economy in industrial chemistry and environmental engineering. It surpasses a mere examination of principles and methods, delving into the profound significance and urgency of this transformative shift. By analyzing key elements such as resource efficiency, waste valorization, sustainable product design, industrial symbiosis, and policy integration, the study highlights the power of collaboration, technological advancements, and extensive literature research. It reveals the remarkable alignment between the circular economy and the Sustainable Development Goals (SDGs), emphasizing how circular practices promote resource efficiency, waste reduction, and sustainable production and consumption patterns, thus driving progress across multiple SDGs. With a specific focus on responsible consumption and production, clean energy, innovative industrial practices, climate action, ecosystem protection, water resource management, job creation, economic growth, sustainable urbanization, and collaboration, the review provides a comprehensive roadmap for adopting circularity. Its practical recommendations cover sustainable material selection, resource efficiency, closing loop, digitalization, and robust policy support. In addition, it emphasizes the paramount importance of collaboration, stakeholder engagement, education, capacity building, circular supply chain management, and effective policy frameworks in spearheading circular economy initiatives. Drawing inspiration from diverse circular economy models and compelling case studies in industrial chemistry, the study highlights the integration of environmental, social, and governance (ESG) factors, ensuring both sustainability and positive societal impact. This comprehensive review serves as a guiding light, demonstrating the immense potential of the circular economy in driving sustainable development. It offers actionable guidance for implementing circular practices, empowering professionals to make tangible contributions to a more sustainable future. Additionally, it serves as a foundational piece, fueling the advancement of knowledge, inspiring further research, and propelling remarkable progress in the ever-evolving fields of industrial chemistry and environmental engineering.